Transcutaneous electrical acupoint stimulation for reducing cognitive dysfunction in lumbar spine surgery: A randomized, controlled trail - Wang, Li-feng; Liang, Wei-dong; Wang, Bing-yu; Guo, Ming-ling; Zhou, Jian-shun; Chen, Li; Zhong, Mao-lin; Ye, Jun-ming (Frontiers in Aging Neuroscience, 2022)
Objective This study aimed to evaluate the effect of perioperative transcutaneous electrical acupoint stimulation (TEAS) on postoperative cognitive dysfunction (POCD) in older patients with lumbar spine surgery. Methods Older patients (aged 60–80 years old) receiving lumbar spine surgery under general anesthesia were randomly divided into group A, 3-day intervention group; group B, 7-day intervention group; control group C, sham TEAS group, selected “Baihui” (GV 20) and “Dazhui” (GV 14) point was intervened once 30 min before operation with “HANS” transcutaneous electrical stimulation device, and then once a day after operation for 30 min each time. The primary outcome was the incidence of postoperative cognitive impairment assessed by the use of the Mini Mental Rating Scale (MMSE), patients developed POCD according to the Z score method. The secondary outcome was serum interleukin-6 (IL-6), tumor Necrosis factor α (TNF-α), neuron-specific enolase (NSE), and S100β protein levels. Results Three days after surgery, the incidence of POCD in groups A((22.4%)) and B ((18.3%)) were lower than those in group C ((42.9%)) (P < 0.05). There was no significant difference between groups A and B (P > 0.05). Seven days after surgery, the incidence of POCD in group B (18.3%) was lower than that in groups A (26.5%) and B (42.9%), and the comparison between groups B and C was statistically significant (P < 0.05). On the 3rd and 7th days after surgery, the levels of IL-6, TNF-α, NSE, and S100β in the two TEAS groups were lower than those in the sham TEAS group (P < 0.01), but higher than the preoperative levels in the three groups (P < 0.01). Conclusion It seems that Perioperative TEAS intervention could reduce the level of inflammatory factors IL-6, TNF-α in the blood of older patients with lumbar spine surgery, and reduce the incidence of POCD. Clinical trial registration www.chictr.org.cn, identifier ChiCTR2200063030.